Factors Affecting Communication Competency of Farmers in Banka District of Bihar - B.K. Mandal and Dipak De, (Indian Journal of Extension Education, 2013)
An attempt has been made to study the communication competency of farmers with special reference to dissemination ofpaddy cultivation technology. The study was conducted with a sample of 300 farmers drawn randomly from Banka &Rajaun blocks of Banka district of Bihar. The study revealed that the main factors determining the communicationcompetency of farmers were presentation skill, sources of information utilization, innovation proneness and annualincome. Among all the nine variables taken for the study, presentation skill emerged as the single most potent factor indetermining the communication competency of farmers.